2019
DOI: 10.1111/epp.12533
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the invasive whiteflyAleurocanthus spiniferus(Hemiptera: Aleyrodidae) in Greece

Abstract: Aleurocanthus spiniferus (Quaintance) (Hemiptera: Aleyrodidae), commonly known as the citrus (or orange) spiny whitefly, is an important pest of various economic crops such as citrus and tea and causes severe economic losses. It is reported for the first time in Greece, in the island of Corfu (North‐West Greece) on sweet orange trees (Citrus sinensis). Morphological and molecular data has been used for species identification. Sequences of the mitochondrial cytochrome oxidase I (COI) gene from Greek populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
1
20
2
Order By: Relevance
“…In the present study, only two haplotypes (H1 and H2) were found, different from what was recently found in Greece, where four different haplotypes were recorded [16]. Therefore, some conclusions are possible (Figure 2):…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the present study, only two haplotypes (H1 and H2) were found, different from what was recently found in Greece, where four different haplotypes were recorded [16]. Therefore, some conclusions are possible (Figure 2):…”
Section: Discussioncontrasting
confidence: 99%
“…Mitochondrial COI sequencing revealed the presence of two haplotypes in the sampled A. spiniferus (Table 1). BLAST search revealed that both obtained haplotypes belong to mitochondrial haplogroup 2 [9] corresponding to the haplotypes H1 and H2 recently found in Greece, and Greece, Italy, and Montenegro, respectively [16].…”
Section: Osw Characterizationmentioning
confidence: 58%
See 3 more Smart Citations